2006
DOI: 10.1111/j.1365-2265.2006.02658.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pioglitazone and metformin on plasma adiponectin in newly detected type 2 diabetes mellitus

Abstract: Pioglitazone therapy appears to be better in achieving glycaemic control and increasing plasma adiponectin and insulin sensitivity in newly detected type 2 diabetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 48 publications
2
32
0
1
Order By: Relevance
“…The alterations in endocrine and metabolic functions of AT can be explained in terms of ADI, which has inverse correlation with ADN level. It has been reported that the treatment of type-II diabetes mellitus with pioglitazone and metformin resulted in the over-expression and secretion of ADN [36]. Our results show that avocado fruits exhibit hypolipidemic activity maybe partly by raising the level of ADN.…”
Section: Discussionmentioning
confidence: 51%
“…The alterations in endocrine and metabolic functions of AT can be explained in terms of ADI, which has inverse correlation with ADN level. It has been reported that the treatment of type-II diabetes mellitus with pioglitazone and metformin resulted in the over-expression and secretion of ADN [36]. Our results show that avocado fruits exhibit hypolipidemic activity maybe partly by raising the level of ADN.…”
Section: Discussionmentioning
confidence: 51%
“…In obese humans with or without type 2 diabetes, weight reduction results in increased adiponectin levels (5). Moreover, improving insulin sensitivity and reducing insulin levels with insulin-sensitizing glitazones markedly increase adiponectin concentrations, even in the absence of or after adjustment of changes in body weight (7)(8)(9). Adiponectin levels have also been shown to increase with lifestyle intervention that produces a reduction in fat mass (10).…”
mentioning
confidence: 97%
“…Together with the effect brought about by pioglitazone (3,23,24), combined therapy with sarpogrelate is predicted to increase the adiponectin level, and this might lead to the improvement of insulin sensitivity.…”
Section: Discussionmentioning
confidence: 96%